Analisis Kebutuhan Pengembangan Materi Ajar Bahasa Indonesia bagi Penutur Asing Tingkat Dasar pada Topik Transportasi Umum - Safitri, Nur Anita Syamsi; Shafariana, Shafariana; Asdah, Atikah Nurul (Magister Pendidikan Bahasa dan Sastra Indonesia Universitas Jambi, 2025)
This research aims to analyze the need for teaching materials on the topic of public transportation for beginner level Indonesian Language Learners for Foreign Speakers (BIPA). The background of this research is based on the importance of the theme of public transportation as part of the basic communicative competence that foreign speakers need in everyday life in Indonesia. The method used is descriptive qualitative with a needs analysis approach, through data collection in the form of questionnaires, interviews, and reviewing existing teaching material documents. The research results show that basic level BIPA students need teaching materials that contain thematic vocabulary and functional expressions which are equipped with socio-cultural contexts such as price negotiation systems and typical South Sulawesi modes of transportation. In addition, students stated the need for visual and audio media, as well as dialogue-based exercises and role simulations to improve communicative skills in an integrative manner. These findings indicate that BIPA teaching materials need to be prepared contextually, communicatively, and based on learner needs. The implications of this research emphasize the importance of developing teaching materials that are thematically relevant, based on local cultural context, and supported by a needs-based learning approach in the BIPA program.